Aspects of Soteriology in John and Paul - Frey, Jörg; van der Watt, Jan G.; Verheyden, Joseph; van, Jan G. (Mohr Siebeck, 2025)
Aspects of Soteriology in John and Paul
PublicationDate: 20250228
Keywords: New Testament Theology -- Early Biblical Interpretation -- Pauline Epistles -- Effektitivitätsgrundsatz -- Johannine writings -- Micro-Editing -- 1-2 Kings -- Para-Biblical Texts -- Elijah-Elisha Narratives -- 6Q4 -- New Testament theology -- Pauline epistles -- Neues Testament -- Array